Analgesic effectiveness of wound infiltration with bupivacaine versus a mixture of bupivacaine and tramadol for postoperative pain management among parturients undergoing elective cesarean section under spinal anesthesia: A randomized controlled trial - Mesay Milkias; Semagn Mekonnen; Hailemariam Getachew; Hailemariam Mulugeta; Siraj Ahmed; Melkamu Kebede; Belete Destaw; Medhanit Melese; Zemedu Aweke (PLoS ONE, 2025)
Background Post-operative pain is among the major post-cesarean problems, with an incidence ranging from 25.5% to 80%. Despite its simplicity, the effectiveness of wound infiltration with a mixture of bupivacaine and tramadol is still unknown. Therefore, this study aims to compare the analgesic effectiveness of wound infiltration with bupivacaine versus a combination of bupivacaine and tramadol for postoperative pain management among parturients undergoing cesarean section under spinal anesthesia. Methodology A double-blind, parallel, randomized controlled trial was conducted on 60 parturients. Parturients were randomized to take either bupivacaine (B = 30) or a combination of bupivacaine and tramadol (BT = 30). The homogeneity of variance was assessed using Levene’s test, and normality was assessed using the Shapiro-Wilk test. A numeric rating scale was used to measure pain severity. The independent t-test and the Mann-Whitney U test were used, respectively, for parametric and non-parametric data. A generalized estimating equation was used to assess repeated measurements. Result In total, 60 parturients were analyzed with no dropouts. The severity of pain at the 6 th hour was six times greater in the B group compared to the BT group (OR = 6.289, CI, 2.097–18.858, P = 0.001). The mean tramadol consumption was lower in the BT group (140.00 ± 48.066 mg) than in the B group (175.00 ± 34.114 mg), with a statistically significant mean difference of 10.761 (95% CI, 13.459 to 56.541), t (58) = 3.252, P = 0.002, (d = 0.839). The mean first analgesia request time was higher in the mixture of the BT group (367.33 ± 50.099 min) than in the B group (216.33 ± 68.744 min), with a statistically significant difference of 15.530 (95% CI, −182.087 to −119.913), t (58) = 5.6553, P = 0.001. Conclusion Wound infiltration with a combination of bupivacaine and tramadol is more effective than bupivacaine alone for postoperative analgesia in pregnant patients who underwent cesarean section under spinal anesthesia. This clinical trial study was registered at the Pan African Clinical Trial Registry with a unique trial registration number of PACTR202310525672884 (13/10/2023).